The working woman in higher education: reflections of the past, hope for the future. Issue 2 (20th February 2017) - Bulick, Natalie; Frey, Susan
Abstract : Purpose: The purpose of this paper is to review the literature on female faculty and administrators working in higher education, past and present. Design/methodology/approach: Materials were selected based on scholarly impact and reputation of the author. Selections were then examined to assure varied perspectives and wide period coverage. Findings: Throughout the past century, women have made tremendous strides in the pursuit of equity in the academic working environment. However, statistics and personal experiences indicate that much progress is still needed. Research limitations/implications: This bibliography is limited to literature on working female faculty and administrators in the USA. It is intended to provide a broad overview of their past and present working conditions. Materials cover the Colonial period though the present. As such, a brief selection of materials available are included. Although there are much fewer resources that include the women of color experience, whenever possible materials are included. For the purpose of this review, the female student demographic is omitted. As there is a plethora of materials on this subject, it should be examined in a separate bibliography. Originality/value: This bibliography provides students and scholars a brief introduction to research women in higher education which encompasses diverse voices, a wide historical range and contemporary materials.